Internal control of labour remuneration as a component of cost management in a construction company - ZGALAT-LOZYNSKA, Liubov; ZINCHENKO, Myroslava; IVANOVA, Tetyana (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the issue of formation of effective internal control of labour remuneration at construction enterprises as an important component of cost management. The article proposes a methodical approach to organisation of internal control of labour remuneration, identifies its main stages: regulatory and legal support, planning and labour rationing, accounting of working hours and documentation, control over compliance with labour legislation, control of payroll and deductions from the payroll fund, analysis of the structure of the payroll fund and assessment of efficiency of its use, feedback and adjustment of control methods. It is determined that the role of internal economic control is to ensure the correctness of cost accounting, compliance with labour legislation, minimise the risks of cost overruns and develop ways to optimise labour costs. Control contributes to the formation of a transparent system of interaction between the company's departments, efficient use of labour resources, prevention of financial abuse and achievement of strategic goals. The authors emphasise the importance of accounting and analytical support, regulatory frameworks and the use of modern control methods that improve the quality of management decisions. Particular attention is paid to the analysis of the structure of the labour remuneration fund and the efficiency of its use. It has been found that systematic audits, regular monitoring and data analysis help to identify reserves, optimise costs and ensure the competitiveness of the enterprise. It is recommended to introduce a unified information system to integrate accounting and control processes between the enterprise's departments. The study has identified a number of problems in the system of internal control of labour remuneration at construction enterprises, in particular, errors in documentation, difficulties with accounting for liabilities and classification of payments. These processes need to be improved to improve the efficiency of managing personnel costs.